2012
DOI: 10.1080/09670262.2012.741713
|View full text |Cite
|
Sign up to set email alerts
|

Haslea karadagensis(Bacillariophyta): a second blue diatom, recorded from the Black Sea and producing a novel blue pigment

Abstract: A new species of raphid pennate diatom producing a blue pigment, Haslea karadagensis Davidovich, Gastineau & Mouget, sp. nov., was recently isolated from the Crimean coast of the Black Sea (Ukraine). This organism is very similar to the well-known Haslea ostrearia, the first described 'blue' diatom, which produces marennine, the pigment involved in the greening of oysters. The Ukrainian diatom, H. karadagensis, differs slightly from H. ostrearia in the structure of its frustule, and the two organisms are unabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 44 publications
0
34
0
1
Order By: Relevance
“…Less investigated, but with a high antioxidant activity, and therefore as potential antiviral, are the polyphenolic compounds: antioxidants produced by marine algae, such as flavonoids, cinnamic acid, benzoic acid, gallic acid, quercetin [91] and phlorotannins, the latter being found in brown macroalgae [92], or diatoms [93]. Phlorotannins are tannin derivatives exhibiting numerous bioactivities, such as antioxidant, anti-inflammatory [94] antibacterial, and antimatrix metallopeptidases (MMP) activities [95]. Ahn et al [93] reported that phloroglucinol derivative 8,8 -bieckol inhibited the activity of recombinant RT and protease of HIV-1 in vitro.…”
Section: Marine Antioxidants and Antiviral Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Less investigated, but with a high antioxidant activity, and therefore as potential antiviral, are the polyphenolic compounds: antioxidants produced by marine algae, such as flavonoids, cinnamic acid, benzoic acid, gallic acid, quercetin [91] and phlorotannins, the latter being found in brown macroalgae [92], or diatoms [93]. Phlorotannins are tannin derivatives exhibiting numerous bioactivities, such as antioxidant, anti-inflammatory [94] antibacterial, and antimatrix metallopeptidases (MMP) activities [95]. Ahn et al [93] reported that phloroglucinol derivative 8,8 -bieckol inhibited the activity of recombinant RT and protease of HIV-1 in vitro.…”
Section: Marine Antioxidants and Antiviral Activitymentioning
confidence: 99%
“…Another peculiar polyphenol discovered in some diatoms, (Haslea sp.) marennine, presented relevant bioactivity and antiviral properties [95].…”
Section: Marine Antioxidants and Antiviral Activitymentioning
confidence: 99%
“…Another diatom, Haslea karadagensis , also has a blue pigment. Although it has quite different absorption maxima from those of marennine, its similar bioactivity has come to be called marennine-like [ 10 ]. While these unusual pigments occur only in selected species, there are some which are included in the more general group of photosynthetic pigments and are common among diatoms.…”
Section: Introductionmentioning
confidence: 99%
“…29, 401 (2016) This microalga has long been considered the only one within the Bacillariophyceae able to produce such a pigment (Neuville and Daste 1978). Recently, two new species of blue Haslea have been described, one producing a pigment similar to marennine, H. provincialis (Gastineau et al 2016), the other, H. karadagensis, a different pigment but belonging to the same chemical family (Gastineau et al 2012b). Marennine accumulates in the apical regions of the cell before being released into the growth medium (Nassiri et al 1998), allowing the predominance of H. ostrearia due to marennine's allelopathic activity (Pouvreau et al 2007a;Prasetiya et al 2016).…”
Section: Introductionmentioning
confidence: 99%